Proposal guideline: Enhancing Climate Resilience for Smallholder Farmers in Zambia through Solar-Powered Irrigation, Capacity building, and Inclusive Financing. Prebemu Enterprises Ltd - Prebemu Enterprises (Accelerating Impacts of CGIAR Climate Research for Africa, 2024)
This is a proposal for enhancing climate resilience for smallholder farmers in Zambia through solar-powered irrigation, capacity building, and inclusive financing. The project is a partnership between Prebemu Enterprises Ltd and the International Management Institute (IWMI). This project targets climate resilience in smallholder farming communities across Zambia’s Central Province, specifically in Chibombo and Mumbwa districts. By integrating solar-powered irrigation systems, climate-smart seeds, and accessible agricultural financing, the project aims to improve water management and productivity for 7,000 smallholder farmers. Through collaboration with FeedNat Agro Limited, a seed company, and Lupiya, a digital lending platform, farmers will gain access to essential resources, including solar irrigation technologies, improved seeds, and affordable credit.